2022
DOI: 10.1101/2022.08.21.504684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D reconstruction of the cerebellar germinal layer reveals intercytoplasmic connections between developing granule cells

Abstract: The difficulty of retrieving high-resolution, in vivo evidence of the proliferative- and migratory processes occurring in neural germinal zones has limited our understanding of neurodevelopmental mechanisms. Here, we employed a connectomic approach using a high-resolution, serial-sectioning scanning electron microscopy volume to investigate the laminar cytoarchitecture of the transient external granular layer (EGL) of the developing cerebellum, where granule cells coordinate a series of mitotic and migratory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Our results open the way to further investigations on the role of TNTs in the developing embryo. Of interest, several studies, including from our group [34][35][36][37] , support potential implication of TNTs in various developmental processes, such as coordinating cell movement, cell differentiation, and cell proliferation. The current demonstration of the presence of these structures in living organisms strongly indicates that cells have the ability to communicate directly and selectively over considerable distances within tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Our results open the way to further investigations on the role of TNTs in the developing embryo. Of interest, several studies, including from our group [34][35][36][37] , support potential implication of TNTs in various developmental processes, such as coordinating cell movement, cell differentiation, and cell proliferation. The current demonstration of the presence of these structures in living organisms strongly indicates that cells have the ability to communicate directly and selectively over considerable distances within tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have provided evidence for the presence of TNT‐like structures in several in vivo and ex vivo models (Alarcon‐Martinez et al., 2022; Chinnery et al., 2008; Lou, Fujisawa, Morozov, et al., 2012; Pasquier et al., 2013; Pinto et al., 2021). Intriguingly, by using a serial‐sectioning scanning electron microscopy (ssSEM)‐based connectomic approach, we have revealed open‐ended connections between developing granule precursors neurons in the mouse cerebellum (Cordero Cervantes et al., 2023). This suggested that neurons can communicate directly before their synaptic connections are established (Zurzolo, 2021).…”
Section: Commentarymentioning
confidence: 99%
“…Based on the high frequency of TNTs forming between undifferentiated neuronal cell lines, Zurzolo hypothesizes that TNTs could represent an early feature of cell‐to‐cell communication, predating classical synaptic transmissions 51 . Collaborating with J. Lichtman (Harvard University), they applied a connectome approach based on serial‐sectioning‐SEM on a mouse cerebellum cortex volume, revealing the existence of intercellular connections (ICs) in a developing mouse brain 56 . These ICs, observed during cerebellar granule cell migration before synapse formation, support the idea that tunneling connections in the brain might precede synaptic transmission and play a vital role in neuronal migration and the establishment of functional circuits 51 .…”
mentioning
confidence: 99%